Social marketing overview of BRAC Communications: A focus on BRAC Humanitarian Crisis Management Programme - Sultana, Fatema Zinat (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.